Sindicalismo docente e as particularidades organizativas, ideológicas e reivindicativas do magistério público municipal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The general purpose of this thesis was to determine the role that trade unions of public school teachers can play from a classist perspective, considering their organisational, demanding, and ideological contradictions and particularities. In order to do so, we identified the main elements that characterise teacher syndicalism in public city schools and compared them with the theoretical perspectives of the trade union movement, pointing out their limits and possibilities in what refers to a revolutionary activity. Based on the Dialectical and Historical Materialism, this work understands the class struggle as an essential antagonism in history that causes a number of contradictions in capitalist societies. Empirically, we conducted a research on public city teachers by selecting three union entities that represent the three forms of teaching organisation, all located in Southeastern Paraná, Brazil: the regional teacher trade union, a division associated with the Paraná state trade union, and the unions of city public servants. Based on statistical materials – especially from the Interunion Department of Statistics and Socioeconomic Studies (DIEESE) – as well as documents such as statutes and by-laws of union entities, interviews with the directors of the three aforementioned entities, and questionnaires administered to city school teachers, we identified some particular aspects of teacher syndicalism related to its organisation, materiality of teacher union consciousness, and content of its demands. Regarding its organisation, we point out the limits shown by the three union entities in the low number of (local) members, and the fact that their demands are municipalised, although some organisations (such as the regional and state trade unions) favour the expansion of the number of teachers at the base. With respect to the materiality of union consciousness, we highlight the contradiction between the teachers concept of trade unions and their low participation in union struggle. In relation to the demands of teacher trade unions, we noticed their approach to education policies, which represents an advance from the perspective of the legislation of the teaching career, but contradictorily it conditions the union movement to the State policies. We also point out that, even though they have specific demands and join more comprehensive political themes, these teachers tend to take action for demands directly related to their remuneration. Taking into account these particularities, we understand that teachers can have a union activity under a classist and revolutionary perspective as trade unions join the political programmes of the working class, in the dialectics between economics and politics synthesised by Trotsky. This happens because the class unity that overcomes the fragmentation of the struggles among many specific categories is primarily related to the content of the demands, in spite of the organisational and ideological differences that define their heterogeneity. In this regard, teacher syndicalism, including the manifestations found in public city schools, despite its organisational, ideological and demanding contradictions and particularities, is related to the working-class syndicalism and driven by salary demands, so it can perform a union activity that effectively addresses the common interests of all workers following a revolutionary perspective.
Keywords: Magistério Público Municipal; Sindicalismo Docente; Organização sindical; Public City Schools; Teacher Syndicalism; Trade Union; CNPQ::CIENCIAS HUMANAS::EDUCACAO